2004
DOI: 10.1002/cyto.a.20007
|View full text |Cite
|
Sign up to set email alerts
|

Absence of cross‐reactivity between murine Ly‐6C and Ly‐6G

Abstract: BackgroundThe Ly‐6 family has many members, including Ly‐6C and Ly‐6G. A previous study suggested that the anti‐Ly‐6G antibody, RB6‐8C5, may react with Ly‐6Chi murine bone marrow (BM) cells. This finding has been interpreted as cross‐reactivity of RB6‐8C5 with the Ly‐6C antigen, and has been generalized to many hematopoietic cell types, using the terminology Ly‐6G/C. The present study was undertaken to determine whether anti‐Ly‐6G antibodies truly cross‐react with the Ly‐6C antigen on multiple hematopoietic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 29 publications
(25 reference statements)
3
36
1
1
Order By: Relevance
“…Thus, in addition to the depletion of neutrophils in blood and the injured spinal cord, it is possible that the anti-Ly6G/Gr-1 antibody might have depleted monocytoid cells and lymphocytes. Others, however, have not found the RB6-8C5 clone to cross-react with Ly6G (Nagendra and Schlueter, 2004). In our study, we were unable to document obvious changes to monocyte or lymphocyte numbers in blood after SCI as a result of antibody treatment (Fig.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Thus, in addition to the depletion of neutrophils in blood and the injured spinal cord, it is possible that the anti-Ly6G/Gr-1 antibody might have depleted monocytoid cells and lymphocytes. Others, however, have not found the RB6-8C5 clone to cross-react with Ly6G (Nagendra and Schlueter, 2004). In our study, we were unable to document obvious changes to monocyte or lymphocyte numbers in blood after SCI as a result of antibody treatment (Fig.…”
Section: Discussioncontrasting
confidence: 78%
“…Ly6G is the major antigen on mature neutrophils identified by the RB6-8C5 clone (Hestdal et al, 1991;Fleming et al, 1993); the antibody depletes neutrophils in both blood and spleen for up to 2-3 d after injection (Conlan and North, 1994;Rakhmilevich, 1995). The RB6-8C5 anti-Ly6G/Gr-1 antibody, however, has been reported to bind to Ly6C, which is found on a subset of monocytoid cells and lymphocytes (Fleming et al, 1993;Daley et al, 2008), although this cross-reactivity was not observed by others (Nagendra and Schlueter, 2004).…”
Section: Methodsmentioning
confidence: 98%
“…This seems to support the idea that anti-Gr-1 mAb binds to Ly6C with minor avidity when compared with Ly6G, as originally suggested [11]. However, even if some groups have concluded that anti-Gr-1 mAb preferentially binds to either Ly6G or Ly6C, many discrepancies about epitope recognition and competition between Ly6C and Ly6G molecules have been reported [12,13], and Gr-1 expression has been largely used to distinguish monocyte subsets [14]. The F4/80 and CD68 markers, both associated with a monocyte/macrophage phenotype, were principally expressed by the Gr-1 int fraction.…”
Section: Mdsc Subset Phenotypesupporting
confidence: 80%
“…In this study, Ly-6G was used as a marker for granulocytic differentiation. An antigranulocyte receptor 1 Ab (RB6-8C5), which has been widely used for the detection of mouse granulocytes (21,25,26), recognizes both Ly-6G and Ly-6C (22,27). However, the expression of Ly-6C is not restricted to granulocytes, and so, the Ab crossreacts with nongranulocytic lineages such as dendritic cells (28), monocytes (29,30), and a subpopulation of lymphocytes (31).…”
Section: Discussionmentioning
confidence: 99%